Systematic literature review: Penggunaan media pembelajaran digital terhadap kemampuan penalaran matematis - Lilia Gina Febrila; Siti Masitoh (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Existing studies have not yet provided a comprehensive overview, particularly with regard to mathematical reasoning ability. This condition highlights the need for a systematic review to identify research trends, map key findings, and comprehensively evaluate the digital learning media. The purpose of this study was to examine research trends and research results regarding the use of digital learning media on students' mathematical reasoning skills. The research method used is the SLR method. Researchers collected scientific articles through various databases including Google scholar, Garuda, Eric, and Semantic scholar. Through the PRISMA process, 22 articles were obtained that met the inclusion and exclusion criteria. The results of the study showed that: 1) the trend of digital learning media is in 2022, the type of media is digital multimedia, junior high school education level with material on measurement and geometry elements, and quantitative research methods are widely used in research on the use of digital learning media on mathematical reasoning skills; 2) the use of digital learning media contributes positively to improving students’ mathematical reasoning ability so that can become a reference for teachers to apply in learning.